PENTINGNYA PERAN KEGIATAN KEROHANIAN KRISTEN DALAM MEMBANGUN NILAI SPIRITUAL SISWA KRISTEN KELAS XII SMA ISEN MULANG DI ERA GLOBALISASI - Meysa Mardalena Sari; Agus Surya; Agustiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Christian spiritual activities, analyze their role and significance in fostering students' spiritual values, and examine their impact on strengthening the faith and character of twelfth-grade students at SMA Isen Mulang amid the challenges of globalization. The background of this study is based on the reality that the era of globalization has brought greater access to information and the influx of various foreign cultures, which often conflict with Christian values. Therefore, a strong spiritual foundation is needed so that students are not easily influenced by the negative effects of modern developments. This research employed a qualitative approach using a descriptive method. Data were collected through direct observation of spiritual activities, in-depth interviews with students and religious education teachers, as well as documentation studies related to the school's spiritual programs. The findings reveal that the spiritual activities implemented include weekly worship services held every Friday afternoon. Based on expert perspectives, these spiritual activities have proven to be highly important and effective in instilling spiritual values such as faith, love, honesty, responsibility, and hope in God. The implementation of these activities serves as a means of character formation, faith development, and personal growth for students. Through these programs, students are equipped with the ability to distinguish between right and wrong values, critically evaluate global information, and maintain their identity as children of God while living in a diverse and open society. This study concludes that Christian spiritual activities constitute a fundamental pillar of character education at SMA Isen Mulang, complementing students' intellectual development while cultivating strong spiritual maturity to face increasingly complex life challenges.